Clinicopathologic factors linked to oncologic outcomes for renal cell carcinoma with sarcomatoid dedifferentiation: A PRISMA-compliant systematic review and meta-analysis - Shan, Lisong; Shao, Xue; Gu, Liangyou; Wu, Minhong; Lin, Pengxiu; Yu, Zhiling; Chen, Qingsheng; Zhu, Daqing (Frontiers in Surgery, 2022)
Background There are still differences in the prognostic factors of renal cell carcinoma with sarcomatoid dedifferentiation (sRCC). The aim of this study was to evaluate important predictors of survival in patients with sRCC. Patients and methods A comprehensive search of PubMed, Embase, and Cochrane Library was conducted to identify eligible studies. The endpoints embraced overall survival (OS), cancer-specific survival (CSS), and progression-free survival (PFS). Hazard ratios (HRs) and related 95% confidence intervals (CIs) were extracted. Results A total of 13 studies were included for analyses. The pooled results showed that high European Cooperative Oncology Group performance score (HR 2.39, 95% CI 1.32–4.30; P = 0.004), high T stage (HR 2.18, 95% CI 1.66–2.86; P < 0.001), positive lymph node (HR 1.54, 95% CI 1.40–1.69; P < 0.001), distant metastasis (HR 2.52, 95% CI 1.99–3.21; P < 0.001), lung metastases (HR 1.45, 95% CI 1.16–1.80; P < 0.001), liver metastases (HR 1.71, 95% CI 1.30–2.25; P < 0.001), tumor necrosis (HR 1.78, 95% CI 1.14–2.80; P = 0.010), and percentage sarcomatoid ≥50% (HR 2.35, 95% CI 1.57–3.52; P < 0.001) were associated with unfavorable OS. Positive lymph node (HR 1.57, 95% CI 1.33–1.85; P < 0.001) and high neutrophil to lymphocyte ratio (HR 1.16, 95% CI 1.04–1.29; P = 0.008) were associated with unfavorable CSS. High T stage (HR 1.93 95% CI 1.44–2.58; P < 0.001) was associated with unfavorable progression-free survival. Conclusions A meta-analysis of available data identified important prognostic factors for CSS, OS, and PFS of sRCC, which should be systematically evaluated for patient counseling, risk stratification, and treatment selection. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=249449.